PENGARUH PENGGUNAAN SERBUK ZEOLIT SEBAGAI PENGGANTI SEBAGIAN AGREGAT HALUS TERHADAP MUTU BETON K-250 - MUZAYIN, MUHAMMAD; ., Romadhon (Program Studi Teknik Sipil Universitas Narotama, 2023)
Concrete is one of the materials that is generally used for modern building construction needs which is very important so that the building becomes sturdy and strong and resistant to weather. Zeolite is a mineral resulting from volcanic ash that settled and froze for tens to hundreds of millions of years ago. The purpose of this study is to determine the effect of zeolite powder as a substitute for some fine aggregates on the compressive strength of K-250 concrete and To find out the mix design of adding zeolite powder to the quality of concrete. The method used in this study is a concrete material practicum guide of Lamongan Islamic University (UNISLA). Based on the results, the research conducted on laboratory tests at the age of 28 days with a mixture of zeolite powder 0% variation worth 21.16 Mpa, 5% variation worth 17.57 Mpa, 10% variation worth 15.59 Mpa, and 15% variation worth 13.46 Mpa. From the mixture of zeolite powder use variations of 5%, 10%, and 15% cannot meet the compressive strength of K-250 because for K-250 concrete at least concrete with a strength of 21.16 Mpa, for a mixture of 5%, 10% and 15% has not met the quality standards of compressive strength of K-250 concrete.